Antifibrotic effects of ZK14, a novel nitric oxidedonating biphenyldicarboxylate derivative, on rat HSC-T6 cells and CCl4-induced hepatic fibrosis - Dai Li; Ji Hui; Kong Xiang-wen; Zhang Yi-hua (Acta Pharmacologica Sinica, 2016)
Aim: To study the pharmacologic effect of ZK14, a novel nitric oxide-donating biphenyldicarboxylate (DDB) derivative, on HSC-T6 cells and on CCl4-induced hepatic fibrosis. Methods: Inhibition of HSC-T6 cell growth by ZK14 was evaluated by MTT assay. The effect of ZK14 on the percentage of HSC-T6 cells undergoing apoptosis was measured using Annexin-V/PI double-staining and TUNEL assay. Mitochondrial membrane potential (MMP) and caspase activities were tested. Hepatic fibrosis was induced in Sprague-Dawley rats by intraperitoneal injection with 14% CCl4. Rats with hepatic fibrosis were randomly divided into four groups: model control, ZK14 (20 mg/kg), ZK14 (10 mg/kg) and DDB (5 mg/kg). Levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), hyaluronic acid (HA), type III collagen (PCIII), and nitric oxide (NO) were assessed, and liver samples were stained with hematoxylin-eosin. The NO level in cells treated with ZK14 in vitro was also measured. Results: The effect of ZK14 on HSC-T6 cell apoptosis was concentration- and time-dependent, with up to 50% of cells becoming apoptotic when exposed to 100 μmol/L ZK14 for 18 h. ZK14 treatment resulted in mitochondrial membrane depolarization and activation of caspases 3 and 9. At a dose of 20 mg/kg, ZK14 significantly decreased serum transaminase (AST, ALT) activities and fibrotic index (HA, PCIII) levels and significantly inhibited fibrogenesis. Conclusion: These data indicate that ZK14, a novel NO-donating DDB derivative, promotes HSC-T6 apoptosis in vitro through a signaling mechanism involving mitochondria and caspase activation and it inhibits CCl4-induced hepatic fibrosis in vivo. The results suggest that ZK14 has potential therapeutic value in the treatment of hepatic fibrosis.